المشاركة الفاعلة لمديري الأقسام في المديريات العامة للتربية في عملية صنع القرار (Journal Of Educational and Psychological Researches, 2013)
The Decision Making Process (DMP) is considered the vital from the point of view intellectuals.  That is because of its effect on performance and the level of productivity of the workers in any organization. In the educational organization in particular, it plays a pivotal role in the technical, managerial and supervision fields.  In addition to the productivity there was a great effect on the moral of the workers in all part of the organization, self respect and the problem solving approach to all work difficulties and challenges.  All that leads to a better working environment where goals are achieved in a collaborative effort.     According to the above, this research aspires to achieve the following:• To recognize the level of the participation in the DMP in the Directorate general of education in Baghdad from the division managers.• The variation that affects the calculation of the results of participation in the DMP from the length of service experience, (more/less than ten years in actual service).  This research was done on the division managers in the directorate general of education in Baghdad area, for the academic year (2012-2013). Sixty participants were chosen randomly.  from the 65% of the allocated study of 108 division manager,  which is the total figure. A 32 point questioner was composed for this research.  To grant the measure the actual level of participation of the studied group. The result was: A very low level of participation was detected, which meant that there was negligible difference in the answers that were given by participants with more or less than ten years in service